Democracy and Human Rights on Bobbio´s Political Theory (2005)
This text accounts for the conceptual tension between democracy and human rights in the general theory of politics of Norberto Bobbio; hence, I try to answer the following questions: How does Bobbio interweave his procedural concept of democracy with the